2015
DOI: 10.1007/s00216-015-9086-3
|View full text |Cite
|
Sign up to set email alerts
|

Simultaneous determination of 18 d-amino acids in rat plasma by an ultrahigh-performance liquid chromatography-tandem mass spectrometry method: application to explore the potential relationship between Alzheimer’s disease and d-amino acid level alterations

Abstract: D-Amino acids are increasingly being recognized as important signaling molecules, and abnormal levels of D-amino acids have been implicated in the pathogenesis of Alzheimer's disease. To evaluate the potential relationship between Alzheimer's disease and D-amino acids, a simple, sensitive, and reliable UPLC-MS/MS method with pre-column derivatization was developed and validated for simultaneous determination of 18 D-amino acids in rat plasma. The analytes were extracted from plasma samples by a protein precipi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
28
0
4

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(32 citation statements)
references
References 32 publications
0
28
0
4
Order By: Relevance
“…Although D-Ser is suggested to become a promising diagnostic biomarker for AD because of the low amount of D-Ser in the brain and plasma of AD model mice in comparison with that of the healthy control model 27,28 , a clear correlation between D-Ser levels in human serum and cognitive function has not been reported 29 . Conversely, in the present study, we found that the amount of D-Ser gradually increased along with cognitive decline.…”
Section: Discussionmentioning
confidence: 99%
“…Although D-Ser is suggested to become a promising diagnostic biomarker for AD because of the low amount of D-Ser in the brain and plasma of AD model mice in comparison with that of the healthy control model 27,28 , a clear correlation between D-Ser levels in human serum and cognitive function has not been reported 29 . Conversely, in the present study, we found that the amount of D-Ser gradually increased along with cognitive decline.…”
Section: Discussionmentioning
confidence: 99%
“…In general, amino acid enantioseparation methods can include CE [44,45], GC [46][47][48][49][50][51][52], MEKC [53,54], HPLC [55,56], and UHPLC [57,58] as well as others (references provided here are for example purposes only, as many others exist). However, HPLC separation methods appear to prevail in the literature for AAR archaeological or paleontological dating purposes.…”
Section: Chromatography Section/ Separationsmentioning
confidence: 99%
“…The determination of chiral metabolites in different sample groups is currently in progress in the authors' laboratory. Xing et al developed and validated the UPLC/MS/MS method with pre-column derivatization with (S)-NIFE for the rapid and simultaneous determination of 18 D-AAs in complex rat plasma [86]. Derivatization in combination with MS/MS detection provided excellent sensitivity.…”
Section: Chromatographic Determination Of Aas As Possible Biomarkers mentioning
confidence: 99%